Design coordination in design development using building information modeling - Leong, Kuan Yoke (2014)
Ambiguity in design, requires coordination among multidisciplinary profession, activities and information which are lively during the design process. Although efforts have been made throughout the decades, the lack of coordination among building designers are still the major problem in the construction industry. Developing technology nowadays have given a huge opportunity for improvement to take place. The product 'from the Building Information Modeling (BIM), building information models are capable to aid designers in coordinating multiple designs and assist the planning work. However, knowledges are required to develop these models and to help in the coordination process. In this paper, we describe our final findings into clashes. It describes current practice in the industry and the revised coordination process using BIM, required knowledge, and development of building information models. These results verify the usefulness of securing the distributed knowledge needed and of developing a building information model to aid with the coordination process.